2016
DOI: 10.3892/br.2016.657
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the T-cell subpopulations in the granulation tissues of chronic suppurative otitis media

Abstract: The present study aimed to investigate the potential involvement of specific T-cell subpopulations in granulation tissue formation in chronic suppurative otitis media (CSOM). Fifteen patients with CSOM were enrolled in this study. Granulation tissues were obtained from the middle ear cavity. Hematoxylin and eosin staining was performed for histopathological observation, and different T-cell subpopulations were characterized by immunohistochemistry. No evident association was identified between granulation tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…6 In fact, it has been reported that Tregs accumulate in the middle ear cavity and nasal mucosa in patients with otitis media and rhinosinusitis. 7,8 Even in a mouse model of otitis media induced by NTHi, Tregs accumulated in the middle ear mucosa. 9 On the basis of these reports, Tregs may affect mucosal immune responses against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…6 In fact, it has been reported that Tregs accumulate in the middle ear cavity and nasal mucosa in patients with otitis media and rhinosinusitis. 7,8 Even in a mouse model of otitis media induced by NTHi, Tregs accumulated in the middle ear mucosa. 9 On the basis of these reports, Tregs may affect mucosal immune responses against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…World Health Organization (WHO) label the individual as patient of CSOM just after 14 days of ear discharge however, otolaryngologists wait for more than three months for the same condition. Clinically, the chronic suppurative otitis media manifests as noteworthy practical restrictions of hearing.7.8.9 In unindustrialized republics, infections of ear and hearing loss are habitually mistreated complaint owing to work force, insufficient funds, knowledge and facilities.10 However, by advances in hygiene, housing, and use of antibiotic in industrialized republics, the frequency of chronic suppurative otitis media has considerably reduced but it still signifies a hazardous a i l m e n t w i t h s e v e r e d i f f i c u l t i e s l i k e 11,12,13 cholesteatoma.…”
mentioning
confidence: 99%